Detection of PDR5-mediated alachlor efflux using a chemically induced dimer biosensor - Hadar Dubkin; Gil Zimran; Assaf Mosquna (PLoS ONE, 2025)
The development of herbicide-resistant crops is a key strategy for achieving efficient and sustainable agriculture. Herbicide tolerance can be conferred by transporters that mediate the efflux of herbicides, making them of particular interest for resistance development. However, identifying a transporter for a specific compound can be a challenging task. Here, we demonstrate the use of a synthetic, yeast two-hybrid-based molecular biosensor to identify transporter activity. A previously engineered biosensor responsive to the herbicide alachlor was utilized to monitor cytosolic alachlor levels in yeast, allowing for the evaluation of candidate transporters. A biosensor-reported shift in alachlor accumulation indicated the Saccharomyces cerevisiae transporter PDR5 as a potential mediator of alachlor efflux. PDR5’s effect on alachlor accumulation was suppressed by a known competing substrate of the transporter, validating its alachlor efflux activity. The ability of the biosensor yeast platform to report transporter activity and its inhibition via a fluorescence output underscores its potential as a tool for transporter-focused research.